A survey of welding robot intelligent path optimization - Wang, Xuewu; Zhou, Xin; Xia, Zelong; Gu, Xingsheng (Journal of manufacturing processes, 2021)
Welding robots are widely used for most welding works in manufacturing industries due to their flexible, efficient and accurate operation. At the same time, it can improve enterprise competitiveness, productivity, product quality, and reduce producing cost. For industrial welding robot task planning, manual planning is still widely used, and it is time-consuming when there are large-scale welding joints or welding seams. To meet this challenge, automatic and efficient path optimization technologies have been studied to realize effective robot path planning. For welding robot path optimization, path optimization problem description is presented first. Then, intelligent optimization algorithms for welding robot path optimization are introduced. Furthermore, obstacle avoidance strategies are studied. Besides, welding robot multi-objective path optimization is given based on the above optimization problem description and optimization algorithm analysis. Optimization results show the effectiveness of intelligent path optimization strategies. At last, the discussions on welding robot path optimization application and future research are analyzed briefly.